Ecología del desarrollo, reproducción y alimentación de anchoas (Osteichthyes: Engraulidae) en un sistema estuarino tropical protegido - Morgado Dueñas, Guadalupe (Universidad Autónoma Metropolitana, 2024)
Engraulids are an important group due to the commercial value of certain species, as well as being the source of food for other commercially important species. Ecologycally, they are the link between primary production and fish of higher trophic levels, thus allowing the flow of energy in the food web. Information about their biological processes, as well as their interactions with their environment, allows to generate relevant information for a better understanding of population dynamics and thus implement an adequate management of them. The aim of this study was to identify the influence of environmental conditions on the development, reproduction and feeding strategies of three species of anchovies in a tropical system. Fish collections were carried out monthly, sampling every two hours until completing a 24-hour cycle. In total, 18 sampling cycles were carried out, from May 2012 to October 2013. The capture of the specimens was done using a beach seine with a 1 cm mesh size. Abiotic and biotic variables in situ were recorded, such as water temperature, salinity, dissolved oxygen, zooplankton and phytoplankton density, and chlorophyll a concentration, in addition to considering historical monthly averages of atmospheric temperature and precipitation. Abiotic and biotic variables in situ were recorded, such as water temperature, salinity, dissolved oxygen, zooplankton and phytoplankton density, and chlorophyll a concentration, in addition to considering historical monthly averages of atmospheric temperature and precipitation. Specimens were counted and identified at species level. Individuals of the three most abundant species Anchoa mitchilli, A. lamprotaenia and A. hepsetus were weighed (g) and measured (mm) to calculate their condition factor. The type of growth was identified using weight-length relationships. Their slopes were compared between species via Analysis of Covariance (ANCOVA) to identify differences in their growth rate. With the Bhattacharya method a modal progression analysis was performed to obtain the growth parameters by species and the von Bertalanffy model. A subsample of specimens of each species was eviscerated to calculate the sexual ratio using a Chi-square analysis (X2 ), the gonadosomatic index (GSI), fecundity, the hepatosomatic index (HSI) and to analyze the stomach contents to calculate their repletion index, to know their trophic niche amplitude by applying the Shannon-Wiener index and to compare the diets between species with a Similarity Analysis (ANOSIM). Finally, each result obtained was analyzed by a Permutational Analysis of Variance (PERMANOVA) at temporal level, between sizes and between sexes to recognize significant differences between these factors and subsequently correlated (Spearman Correlation) with the environmental variables to identify associations. As a result, was determined that the three species have positive allometric growth. The sizes of the three species vary significantly between months and between day and night. The von Bertalanffy growth parameters for A. mitchilli are L∞ = 79.18 mm, k = 0.9 year -1 and t0 = 0.049; for A. lamprotaenia, L∞ = 94.74 mm, k = 1.25 year -1 and t0 = 0.009 and for A. hepsetus, L∞ = 133.67 mm, k = 0.91 year -1 and t0 = 0.018. The condition factor of the three species varied significantly between months. The sex ratio of A. mitchilli and A. hepsetus was 1:1 and of A. lamprotaenia was 1:2.269, with females dominating, in all three cases, variations were observed throughout the year. The proportion of males increased during the months close to the reproductive season which, according to the IGS for A. mitchilli occurs between June-July and January-April. For A. lamprotaenia in April and January-April for A. hepsetus. This index was higher in females of A. lamprotaenia and A. hepsetus ( =1.37 and 0.74 respectively) but was higher in males of A. mitchilli ( = 3.21). The fecundity of the three species was significantly related to the size of the specimen, therefore, A. hepsetus was the species with the highest fecundity ( = 3523) and A. mitchilli, the least ( = 2692). Salinity, temperature, and chlorophyll a were the most important variables on the growth rate, condition factor and reproductive season of the species. In the stomach content analyses, a total of 28 food groups were identified. A. lamprotaenia was the one with the highest dietary diversity index, while A. mitchilli was the least diverse. In all three species, predominated copepods, zoea larvae, megalopa larvae and fish larvae, but significantly changing their relative abundance between months, between day and night, and between sizes. The diet of the three species varied significantly, with A. mitchilli and A. lamprotaenia having the greatest difference in their diets (R = 0.153, p = 0.001), A. lamprotaenia and A. hepsetus having the greatest similarity (R = 0.068, p = 0.001). In conclusion, the three species presented similarities in terms of reproduction, feeding and growth, however, differences were observed in terms of reproductive season, type of feeding and physiological optimum, which is what allows them to use the same resources at different times of the year or daytime hours, allowing them to achieve coexistence in the system.; Los engraulidos son un grupo de peces importantes por el valor comercial de ciertas especies, así como por ser fuente de alimento de otras de importancia comercial. Ecológicamente, son el enlace entre la producción primaria y los peces de niveles tróficos superiores, permitiendo así el flujo de energía en la red trófica. Información sobre sus procesos biológicos, además de las interacciones de éstos con su entorno, permite tener una mejor comprensión sobre su dinámica poblacional que permita implementar estrategias de manejo adecuadas para el uso sostenible de sus poblaciones. El objetivo de este estudio fue identificar la influencia que ejercen las condiciones ambientales sobre las estrategias de desarrollo, reproducción y alimentación de tres especies de anchoas en un sistema tropical. De mayo del 2012 a octubre del 2013, se realizaron colectas mensuales de peces muestreando cada dos horas hasta completar un ciclo de 24 horas. En total se realizaron 18 ciclos de muestreo. Los especímenes se capturaron con un chinchorro playero con red de 1 cm de luz de malla. Se registraron variables abióticas y bióticas in situ como temperatura del agua, salinidad, oxígeno disuelto, densidad de zooplancton y fitoplancton y concentración de clorofila a además de considerar promedios históricos mensuales de temperatura atmosférica y precipitación. Se seleccionaron como objeto de estuvo a tres especies: Anchoa mitchilli, A. lamprotaenia y A. hepsetus. A partir de la relación pesolongitud se estimó el factor de condición y el tipo de crecimiento Con el método de Bhattacharya se hizo un análisis de progresión modal para obtener el modelo de crecimiento de von Bertalanffy. Se evisceró una submuestra de ejemplares de cada especie para calcular la proporción sexual, el índice gonadosomático (IGS), la fecundidad y el índice hepatosomático (IHS). A partir del análisis del contenido estomacal se calculó el índice de repleción. La amplitud del nicho trófico se obtuvo con el índice de Shannon-Wiener y a partir del Análisis de Similitud se compararon las dietas entre especies. . Finalmente, se aplicó un Análisis de Varianza Permutacional a nivel temporal, entre tallas y entre sexos para reconocer diferencias significativas entre los factores estimados y posteriormente se correlacionaron con una Correlación de Spearman con las variables ambientales para identificar asociaciones. Como resultado se determinó que las tres especies tienen crecimiento alométrico positivo. Las tallas de las tres especies varían significativamente entre meses y entre el día y la noche. Los parámetros de crecimiento de von Bertalanffy para A. mitchilli son L∞ = 79.18 mm, k = 0.9 año-1 y t0 = 0.049; para A. lamprotaenia, L∞ = 94.74 mm, k = 1.25 año-1 y t0 = 0.009 y para A. hepsetus, L∞ = 133.67 mm, k = 0.91 año-1 y t0 = 0.018. El factor de condición de las tres especies varió significativamente entre meses. La proporción sexual de A. mitchilli y A. hepsetus fue de 1:1, y de A. lamprotaenia de 1:2.3, dominando las hembras, en los tres casos se observaron variaciones a lo largo del año. La proporción de machos aumentó durante los meses cercanos a la época reproductiva, que, con base en el IGS, en A. mitchilli ocurre entre junio-julio y enero-abril, para A. lamprotaenia en abril, y en A. hepsetus de enero-abril. Este índice fue mayor en hembras de A. lamprotaenia y de A. hepsetus (× =1.37 y 0.74 respectivamente), pero fue mayor en los machos de A. mitchilli ( = 3.21). La fecundidad de las tres especies se relacionó significativamente con la talla de los individuos, siendo A. hepsetus la especie con mayor fecundidad (× = 3523) y A. mitchilli, la menor (× = 2692). La salinidad, temperatura y clorofila a fueron las variables más importantes sobre la tasa de crecimiento, el factor de condición y la época reproductiva de las especies. En los análisis de contenido estomacal, en total se identificaron 28 grupos alimenticios. A. lamprotaenia tuvo el mayor índice de diversidad alimenticia, mientras que A. mitchilli fue la menos diversa. En las tres especies, predominaron los copépodos, larvas zoea, larvas megalopa y larvas de peces, cambiando significativamente su abundancia relativa entre meses, entre el día y la noche, y entre tallas. La dieta de las tres especies varió significativamente, siendo A. mitchilli y A. lamprotaenia quienes tienen mayor diferencia en sus dietas (R = 0.153, p = 0.001), y A. lamprotaenia y A. hepsetus quienes tienen mayor similitud (R = 0.068, p = 0.001). En conclusión, las tres especies presentaron similitudes en cuanto a reproducción, alimentación y crecimiento, sin embargo, se observaron diferencias en cuanto a época reproductiva, tipo de alimentación y óptimos fisiológicos es lo que les permite utilizar los mismos recursos en diferentes momentos del año u horas del día, lo cual les permite coexistir en el sistema. Palabras clave: Boquerones, Sitio Ramsar, Biología, Reparto de recursos, Coexistencia.